PRODUCTION OF METHANOL FROM C02 USING ZnFe204-Ti02 PHOTOCATALYST UNDER VISIBLE LIGHT IRRADIATION - IQBAL, FARUKH (2017)
C02 is major gas contributing in global warming. Conversion of C02 into a various product like methanol under visible light irradiation is very attractive since last century. The production of renewable fuel from carbon dioxide photoreduction using visible light irradiation has gained remarkable attention due to inadequate availability of carbon-based fuel and global warming issue. The aim of current research work is to synthesize a visible light active photocatalyst for reduction of carbon dioxide into methanol under visible light irradiation. This research is based on the profound analysis of published work, which allows selection of appropriate methods and material for this research.